Hip Pain in Athletes: Part 1—How to Work Up, Diagnose, and Manage Core Muscle Injuries (Athletic Pubalgia) - Poor, Alexander E.; Roedl, Johannes B.; Zoga, Adam C.; Meyers, William C. (The Journal of Hip Surgery, 2018)
Lower abdominal and groin injuries are among the most common causes of pain in athletes. Those that involve the skeletal muscles of the core, defined as the entire body from the chest to the midthigh, are called core muscle injuries. In this review, the authors will describe the anatomy and pathophysiology of core muscle injuries in detail, as well as the appropriate work-up and management. Special consideration is given to the important interrelationship between core muscle injuries and intrinsic hip pathology, such as femoroacetabular impingement, and to the drawbacks of treating these injuries with platelet-rich plasma.
Keywords: sports hernia; athletic pubalgia; core muscle injury; femoroacetabular impingement